Accounting Accruals and Auditor Reporting Conservatism* - FRANCIS, JERE R.; KRISHNAN, JAGAN (Contemporary Accounting Research, 1999)
Accounting accruals are managers' subjective estimates of future outcomes and cannot, by definition, be objectively verified by auditors prior to occurrence. This causes audits of high‐accrual firms to pose more uncertainty than audits of low‐accrual firms because of potential estimation error and a greater chance that high‐accrual firms have undetected asset realization and/or going concern problems that are related to the high level of accruals. One way that auditors can compensate for this risk exposure is to lower their threshold for issuing modified audit reports, an action that will increase modified reports and, therefore, lessen the likelihood of failing to issue a modified report when appropriate. We call this auditor reporting conservatism and test if high‐accrual firms in the United States, are more likely to receive modified audit reports for asset realization uncertainties and going concern problems. Empirical results for a large sample of U.S. publicly listed companies support the hypothesis that auditors are more conservative, that is, more likely to issue both types of modified audit reports for high‐accrual firms. Further analyses show that income‐increasing accruals are somewhat more likely to result in reporting conservatism than income‐decreasing accruals, and that only the Big Six group of auditors show evidence of reporting conservatism. These findings add to our understanding of the audit report formation process and the potentially important role played by accounting accruals in that process.